2004
DOI: 10.1088/0953-8984/16/23/021
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of radiation-induced magnetoresistance oscillations in high-mobility two-dimensional electron systems

Abstract: We present a detailed theoretical investigation of the radiation induced giant magnetoresistance oscillations recently discovered in high-mobility twodimensional electron gas. Electron interactions with impurities, and transverse and longitudinal acoustic phonons in GaAs-based heterosystems are considered simultaneously. Multiphoton-assisted impurity scatterings are shown to be the primary origin of the resistance oscillation. Based on the balance-equation theory developed for magnetotransport in Faraday geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…According to theory, [31,34,36]steady state microwave excitation can heat a high mobility two-dimensional electron system. The energy gain from the radiation field is balanced by energy loss to the lattice by electron-phonon scattering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to theory, [31,34,36]steady state microwave excitation can heat a high mobility two-dimensional electron system. The energy gain from the radiation field is balanced by energy loss to the lattice by electron-phonon scattering.…”
Section: Discussionmentioning
confidence: 99%
“…A further topic of experimental interest is to examine the possibility of electron heating, as theory has, [31,34,36] in consistency with common experience, indicated the possibility of microwave-induced electron heating in the high mobility 2DES in the regime of the radiation-induced magnetoresistance oscillations. Not surprisingly, under steady state microwave excitation, the 2DES can be expected to absorb energy from the radiation field.…”
Section: Introductionmentioning
confidence: 86%
“…Most of the theoretical work suggests that the origin of the ZRS is closely related to a negativeresistance instability that occurs in the system due to the combined effect of quantized Landau levels and photonassisted scattering. [3][4][5][6][7]12 It was proposed that the ZRS can be explained if the current-dependent resistance of the system which becomes negative at small current ͑for strong enough microwave radiation͒ becomes positive again when the current j ជ becomes large enough. [3][4][5][6][7] The above physics was put together phenomenologically into an equation…”
mentioning
confidence: 99%
“…[3][4][5][6][7]12 It was proposed that the ZRS can be explained if the current-dependent resistance of the system which becomes negative at small current ͑for strong enough microwave radiation͒ becomes positive again when the current j ជ becomes large enough. [3][4][5][6][7] The above physics was put together phenomenologically into an equationwhere R͓j͔ is a phenomenological current-dependent resistance which is negative at j = 0, increases as a function of j and passes through zero at ͉j ជ ͉ = j o , 7 E ជ d is the applied dc electric field and H is the ordinary Hall resistivity. It was suggested that Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation